Back Cover Image, Volume 91, Number 2, February 2019. Issue 2 (12th December 2018) - Samwel, Kandali; Kahesa, Crispin; Mwaiselage, Julius; Gonzalez, Daniela; West, John T.; Wood, Charles; Palefsky, Joel; Angeletti, Peter C.
Abstract : Cover Caption : The cover image is based on the Research Article Analytical performance of a low-cost multiplex polymerase chain reaction human papillomavirus genotyping assay for use in Sub‐Saharan Africa, by Kandali Samwel et al., DOI10.1002/jmv.25329 .